PENGEMBANGAN SISTEM INFORMASI KEMAJUAN AKADEMIK MENGGUNAKAN MODEL INCREMENTAL BERBASIS EVALUASI USABILITY DAN WHITE BOX TESTING - I Made Agus Oka Gunawan; Gede Indrawan; Sariyasa Sariyasa (LPPM STMIK STIKOM Indonesia, 2021)
This research aims to develop an Academic Progress Information System (SIsKA) in the Computer Science Study Program, Postgraduate Program at Ganesha University of Education. The incremental development model is used in the development of SIsKA. The evaluation stage is carried out using the Focus Group Discussions technique to validate user input for the development stage. Evaluation was carried out on 20 respondents, who were selected using simple random sampling technique from active SIsKA users. Testing of the SIsKA development code is also carried out using White Box Testing. The results of the evaluation of phase 1 and phase 2 of development succeeded in providing recommendations for improvements according to user needs. The evaluation results from phase 3 of development show that SIsKA is in accordance with user needs. The results of the White Box test show that all lecturer page functions are at a simple level. Future development and evaluation can focus on improving the complexity of the 14 functions on the administrator and student pages, as well as analyzing data security related to SIsKA.